Phosphane–ene chemistry: the reactivity of air-stable primary phosphines and their compatibility with the thiol–ene reaction1. Issue 35 (21st September 2015) - Guterman, Ryan; Gillies, Elizabeth R.; Ragogna, Paul J.
<x xml:space="preserve">Abstract</x> Air-sensitive and air-stable primary phosphines (RPH2) were compared for their ability to undergo photoinitiated phosphane–ene chemistry with 1-hexene.